Navigating parental requests: considering the relational potential standard in paediatric end-of-life care in the paediatric intensive care unit - Kingsley, Jenny (Journal of medical ethics, 2025)
Families and clinicians approaching a child's death in the paediatric intensive care unit (PICU) frequently encounter questions surrounding medical decision-making at the end of life (EOL), including defining what is in the child's best interest, finding an optimal balance of benefit over harm, and sometimes addressing potential futility and moral distress. The best interest standard (BIS) is often marshalled by clinicians to help navigate these dilemmas and focuses on a clinician's primary ethical duty to the paediatric patient. This approach does not consider a clinician's potential duty to the patient's family. This paper argues that when a child is dying in the PICU, the physician has a duty to serve both the patient and the family, and that in some circumstances, the duty to serve the family becomes as important as that owed to the child. We detail the limitations of the BIS in paediatric EOL care and propose the relational potential standard as an additional ethical framework to guide our decisions.